'It doesn't seem like PE and I love it': Adolescent girls' views of a health club physical education approach. (February 2019) - Timken, Gay; McNamee, Jeff; Coste, Sarah
School-based physical education (PE) is the most efficient and cost-effective means of increasing girls' physical activity. Therefore, this project used a health club (HC) approach to alter a high school PE experience for 17 grade nine girls (M age = 14.6 ± .49). As part of a larger mixed-methods study, this qualitative element gauged adolescent girls' perceptions of their HC experience using the frameworks of interpretive description and practice-referenced research. Students participated in both pre- and post-intervention semi-structured focus group interviews and completed journals throughout the 14-week intervention. Results revealed autonomy as one organizing theme, including students reporting the importance of choice, variety, and novelty. A second organizing theme was relatedness, with subthemes specific to how girls appreciated having a single-gender PE experience, and their desire for a positive relationship with the research assistants who were leading the experience at the health club.